Role of regional wetland emissions in atmospheric methane variability. Issue 21 (12th November 2016) - McNorton, J.; Gloor, E.; Wilson, C.; Hayman, G. D.; Gedney, N.; Comyn‐Platt, E.; Marthews, T.; Parker, R. J.; Boesch, H.; Chipperfield, M. P.
Abstract: Atmospheric methane (CH4 ) accounts for ~20% of the total direct anthropogenic radiative forcing by long‐lived greenhouse gases. Surface observations show a pause (1999–2006) followed by a resumption in CH4 growth, which remain largely unexplained. Using a land surface model, we estimate wetland CH4 emissions from 1993 to 2014 and study the regional contributions to changes in atmospheric CH4 . Atmospheric model simulations using these emissions, together with other sources, compare well with surface and satellite CH4 data. Modeled global wetland emissions vary by ±3%/yr ( σ  = 4.8 Tg), mainly due to precipitation‐induced changes in wetland area, but the integrated effect makes only a small contribution to the pause in CH4 growth from 1999 to 2006. Increasing temperature, which increases wetland area, drives a long‐term trend in wetland CH4 emissions of +0.2%/yr (1999 to 2014). The increased growth post‐2006 was partly caused by increased wetland emissions (+3%), mainly from Tropical Asia, Southern Africa, and Australia. Plain Language Summary: Methane is the second most important greenhouse gas and its atmospheric concentration is increasing. Currently the reasons for this are poorly understood, with several suspected causes. The main single source of methane to the atmosphere is from microbial activity in wetlands. Using computer models this study shows an increase in emissions from wetlands from 1993–2014, mainly as a result of warming temperatures. This could continue into the future with rising temperatures. The increased emissions were found to be partly responsible for the upward trend in atmospheric methane. The study uses satellite atmospheric methane data to help validate the findings.The growth rate of methane slowed down noticeably for a few years at the turn of the 21st century before resuming again in 2007; previous studies concluded this was likely due to changes in wetland emissions. This study finds that while wetland emissions did decrease for some of the years when the methane atmospheric growth rate stalled, they alone could not explain the entire slowdown in growth. Finally, the study finds increased wetland emissions contributed to some of the growth since 2007. Key Points: An updated land surface model predicts a trend of +0.2%/yr in global wetland CH4 emissions over 1993‐2014, mainly driven by temperature An atmospheric model using these wetland fluxes, along with other emission estimates, agrees well with ground‐based and satellite CH4 data Varying global wetland CH4 emissions (±3%) made a small contribution to the 1999‐2006 pause but contributed ~1 ppb/yr to growth post‐2006